Numerical Simulation of Magnetoelectric Composite for Power Supply of Small Biomedical Devices - Essaket, Soukaina; Idiri, Mohamed; Eddiai, Adil Eddiai; Fadlaoui, Dounia El; Boubeker, Brahim; Ihfa, Fatima Ezahra (International Journal of Membrane Science and Technology, 2023)
This paper introduces a comparative numerical modeling and simulation study of a smart composite material combining piezoelectric ceramics Terfenol-D/GFRP/PZT-5H and Terfenol-D/PZT-5H. The remarkable combination of high output voltage coefficients and substantial power output positions this composite as an ideal candidate for energy transduction applications, particularly in wireless power devices within the field of biomedical applications. Additionally, we explored the potential of PZT-5A to evaluate the feasibility of modeling both piezoelectric and magnetostrictive self-sensing responses under the influence of applied stress. This numerical investigation was complemented by a series of mechanical tests aimed at characterizing the piezoelectric and magnetostrictive responses, as well as the material’s mechanical strength.The results obtained demonstrate the successful accomplishment of active vibration control through the development of a smart self-sensing composite material. This composite harnesses the piezoelectric properties of PZT-5A ceramics and the magnetostrictive properties of Terfenol-D. The remarkable combination of a high output voltage coefficient and substantial power output positions this composite as an exceptional candidate for energy transduction applications, particularly in the realm of biomedical devices requiring wireless power. Specifically, Terfenol-D/GFRP/PZT-5H composite materials show promise for enhancing wireless powering solutions in biomedical applications